Cytological changes and alterations in polyamine contents induced by cadmium in tobacco BY-2 cells - Kuthanová, Andrea; Gemperlová, Lenka; Zelenková, Sylva; Eder, Josef; Machácková, Ivana; Opatrný, Zdenĕk; Cvikrová, Milena (Plant physiology and biochemistry, 2004)
Changes in cell viability, proliferation, cell and nuclear morphology including nuclear and DNA fragmentation induced by 0.05 and 1 mM CdSO4 (Cd2+) in tobacco BY-2 cell line (Nicotiana tabacum L.) were studied in the course of 7 days. Simultaneously changes in endogenous contents of both free and conjugated forms of polyamines (PAs) were investigated for 3 days. The application of 0.05 mM Cd2+ evoked decline of cell viability to approximately 60% during the first 24 h of treatment. Later on degradation of cytoplasmic strands, formation of the stress granules and vesicles, modifications in size and shape of the nuclei, including their fragmentation, were observed in the surviving cells. Their proliferation was blocked and cells elongated. Beginning the first day of treatment TUNEL-positive nuclei were detected in cells cultivated in medium containing 0.05 mM Cd2+. Treatment with highly toxic 1 mM Cd2+ induced fast decrease of cell viability (no viable cells remained after 6-h treatment) and cell death occurred before DNA cleavage might be initiated. The exposure of tobacco BY-2 cells to 0.05 mM Cd2+ resulted in a marked accumulation of total PAs (represented by the sum of free PAs and their perchloric acid (PCA)-soluble and PCA-insoluble conjugates) during 3-day treatment. The increase in total PA contents was primarily caused by the increase in putrescine (Put) concentration. The accumulation of free spermidine (Spd) and spermine (Spm) at 12 and 24 h in 0.05 mM Cd2+ treated BY-2 cells and high contents of Spd and especially Spm determined in dead cells after I mM Cd2+ application was observed. The participation of PA conjugation with hydroxycinnamic acids and PA oxidative deamination in maintaining of free PA levels in BY-2 cells under Cd2+-induced oxidative stress is discussed.
Keywords: buněčné dělení; Cell Line; Nicotiana; Cell Survival; buněčné linie; viabilita buněk; Cell Division; tabák; kadmium; polyaminy; Polyamines; Cadmium